Magmatic arcs and nappes in Myanmar and western Thailand related to Neo-Tethys closure and Indian Ocean subduction - Mitchell, Andrew; Htun, Kyaw Min; Htay, Myint Thein; Htay, Nyunt (Thai Geoscience Journal, 2022)
Our tectonic interpretation of western Myanmar and westernmost Thailand adopts proposed restorations of ca 450 km post-Eocene dextral displacement on the Sagaing Fault and argues that in the Early Jurassic Neo-Tethys lay between convergent subducting oceanic basins, one offshore Sibumasu on the Asian plate, and one offshore a narrow continental Victoria-Katha Block. With basin closures ophiolitic nappes obducted from Neo-Tethys over-rode turbidites on the Asian and Victoria-Katha Blocks’ passive margins, translating the turbidites landward as flysch (deformed or tectonised turbidite) nappes. On the Asian margin crustal thickening in the E-vergent orogen formed the Yinmabin Schist, re-thrust eastwards over the flysch before orogenic polarity reversed and the eastward-subducting Neo-Tethys generated the Early Cretaceous W-facing Mondaung Arc in Myanmar and Thailand. We suggest that on the Victoria-Katha Block’s eastern margin ophiolite obduction was followed by reversal in orogenic polarity, westward subduction of Neo[1]Tethys and Late Cretaceous Popa-Loimye arc magmatism which ended soon after 90 Ma with Neo-Tethys closure, thrusting of the Victoria-Katha Block onto Asia and formation of a suture zone which probably continues into the Nujiang-Bangongco zone in China. Subsequent back[1]thrusting translated metamorphic rocks on the Asian margin westwards, over-riding the Neo[1]Tethys suture zone and Orbitolina Limestone on the Victoria-Katha Block as seen in the Shwebo Basin and north of Mogok. Following crustal shortening, partial melting and intrusion of Western Tin Belt granites at ca 70-44 Ma, orogenic polarity again reversed and eastward subduction of the proto-Indian Ocean generated Late Eocene and younger magmatic rocks of the Popa-Loimye Arc. We argue that most of the copper, gold, tin, tungsten, antimony, jadeite and gemstones in Myanmar west of the Palaeo-Tethys are related to the above orogenic events, although the formation of sapphire, ruby, Shante district gold and Monywa copper were accompanied by dextral displacement on the Sagaing Fault.